Effect of porosity and phase composition in 3D printed calcium phosphate scaffolds on bone tissue regeneration in vivo. (July 2022) - Raja, Naren; Han, Shi Huan; Cho, Minjoon; Choi, Yeong-Jin; Jin, Yuan-Zhe; Park, Honghyun; Lee, Jae Hyup; Yun, Hui-suk
Graphical abstract: Highlights: 3D porous calcium phosphate scaffolds with fast degrading brushite surface covering a bone-like apatite core was prepared at physiological conditions by 3D printing and calcium phosphate cement reaction. Composite brushite-apatite scaffolds showed high compressive strength even with high porosity. Highly porous composite scaffolds showed improved bone regeneration and was completely replaced by new bone by the end of the test period. Compared to conventional bone implants with single composition, brushite-apatite composite scaffolds show promising potential in bone tissue engineering. Abstract: Highly porous calcium phosphate (CaP) scaffolds with multiple phases were fabricated through combination of material extrusion type 3D printing process, salt-leaching, and bone cement chemistry under physiological conditions. Scaffolds with nano-sized calcium deficient hydroxy apatite (CDHA) in the core and large crystals of dicalcium phosphate dihydrate (DCPD or brushite) on the outer surface were fabricated by immersing the 3D ceramic scaffold in aqueous 'cement solution'. In contrast to conventional CaP cement reactions where a single product is obtained, here we could achieve a composite of apatite-brushite. The composite scaffolds showed improved compressive strength without loss of porosity which was suitable for efficient bone tissue regeneration. With 65 % porosity, these scaffolds showed compressive strength of 15 MPa. The porosity of CaP scaffold was increased by applying salt-leaching technique to 3D printing, which greatly influenced the biodegradation of the scaffold in vivo . Composite scaffolds with fast degrading brushite shell showed better and faster scaffold-to-bone integration compared to apatite based scaffold. In vivo studies verified that multi-phase CaP scaffolds with bimodal pore structure induced good new bone formation behavior (85 % of coverage rate on calvaria defect site after 11 weeks of implantation) with good biodegradability (76.6 % of degradation in rabbit subdermal model after 12 weeks of implantation).